Una caracterización sobre las soluciones para el problema de reaprovisionamiento conjunto - de-los-Cobos-Silva, Sergio (2006)
In this paper an introduction is given to a multiple-item inventory problem, known as the Joint Replenishment Problem (JRP). This is a real world problem which has been extensively studied. The JRP has a continuous decision variable, and as many discrete decision variables as products that are ordered and produced. An exact method, given by Goyal, exists for solving the JRP, however for a large number of discrete decision variables the computational time required becomes prohibitive. Here, an alternative characterization of the solution for the combinatorial part of the JRP is given.